Factors Affecting Arab Students’ Selection of Jordanian Universities - Emad Masoud; Lama Al kour (My University, 2015)
This study aimed to investigate factors affecting Arab students’ selection of Jordanian Universities, which include (quality of education services, marketing communication, education cost, physical environment, university location & environmental factors). To achieve the purpose of the study, a structured questionnaire was developedand includes (52) items, the Cronbachs Alpha for the instrument (0.949). A convenience sample technique was used to collect the data from a sample of (375) students distributed over (10) universities in Amman area, (358) questionnaires were returned with response rate (95.46%). The result of the study showed that there was an effect of independant variables on Arab students’ selection of Jordanian universities. Results also revealed that quality of education services, environmental factors, and cost of education were the most factors affecting Arab students’ selection of universities, and there is no difference in their selection according to gender, marital status, and family income, while their selection affected by their nationality. Study also recommends universities to improve the quality of education services, marketing communication and using different promotion tools, specially the web site of the universities. And to pay attention to physical environment like parking, and try to decrease the education cost.

هدفت هذه الدراسة إلى معرفة العوامل المؤثرة في اختيار الطلبة العرب للجامعات الأردنية، والمتمثلة في كل من (جودة الخدمة التعليمية، الاتصالات التسويقية، كلفة خدمات التعليم، البيئة المادية، الموقع الجغرافي للجامعة، والعوامل البيئية). شملت أداة الدراسة على (52) فقرة موزعه على سبعة مجالات هي (جودة الخدمة التعليمية، الاتصالات التسويقية، كلفة خدمات التعليم، البيئة المادية، الموقع الجغرافي للجامعة، العوامل البيئية، والاختيار)، وبلغت الدرجة الكلية للإتساق الداخلي باستخدام اختبار معامل كرونباخ ألفا (0.944). تم تطبيق أداة الدراسة على عينة تكونت من(375) طالباً وطالبة موزعة على (10) جامعات في العاصمة عمان، تم اختيارهم بالطريقة الميسرة، وكانت الاستبانات المستردة والصالحة للتحليل (358) استبانة بنسبة استجابة (95.46)%. أظهرت نتائج الدراسة وجود أثر لكل من المتغيرات المستقلة على اختيار الطلبة العرب للجامعات الأردنية، كما أشارت نتائج الدراسة إلى أن (جودة الخدمة التعليمية والعوامل البيئية وكلفة خدمات التعليم) هي العوامل الأكثر تأثيراً في اختيار الطلبة العرب للجامعات الأردنية التي يدرسون فيها، وعدم وجود فروق في اختيار الطلبة العرب للجامعات التي يدرسون فيها تعزى إلى متغير النوع، والحالةالاجتماعية ودخل الأسرة والتخصص. بينما توجد فروق في اختيار الطلبة العرب للجامعات الأردنية التي يدرسون فيها تعزى إلى متغير الجنسية. وقد أوصت الدراسة بأن تقوم الجامعات بتحسين جودة الخدمة التعليمية، وتعزيز الاتصالات التسويقية، والاهتمام بالوسائل المختلفة لترويج الجامعات الأردنية للطلبة العرب وبخاصه الاهتمام بالموقع الإلكتروني، والاهتمام بالبيئة المادية كالاهتمام بمواقف السيارات مثلاَ، وخفض تكاليف الدراسة حيث لها تأثير في اختيار الطلبة العرب للجامعات الأردنية.
العوامل المؤثرة في اختيار الطلبة العرب للجامعات الأردنية